Regenerative Medicine for the Treatment of Ischemic Heart Disease; Status and Future Perspectives - Arjmand, Babak; Abedi, Mina; Arabi, Maryam; Alavi-Moghadam, Sepideh; Rezaei-Tavirani, Mostafa; Hadavandkhani, Mahdieh; Tayanloo-Beik, Akram; Kordi, Ramin; Roudsari, Peyvand Parhizkar; Larijani, Bagher (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease is now the leading cause of adult death in the world. According to new estimates from the World Health Organization, myocardial infarction (MI) is responsible for four out of every five deaths due to cardiovascular disease. Conventional treatments of MI are taking aspirin and nitroglycerin as intermediate treatments and injecting antithrombotic agents within the first 3 h after MI. Coronary artery bypass grafting and percutaneous coronary intervention are the most common long term treatments. Since none of these interventions will fully regenerate the infarcted myocardium, there is value in pursuing more innovative therapeutic approaches. Regenerative medicine is an innovative interdisciplinary method for rebuilding, replacing, or repairing the missed part of different organs in the body, as similar as possible to the primary structure. In recent years, regenerative medicine has been widely utilized as a treatment for ischemic heart disease (one of the most fatal factors around the world) to repair the lost part of the heart by using stem cells. Here, the development of mesenchymal stem cells causes a breakthrough in the treatment of different cardiovascular diseases. They are easily obtainable from different sources, and expanded and enriched easily, with no need for immunosuppressing agents before transplantation, and fewer possibilities of genetic abnormality accompany them through multiple passages. The production of new cardiomyocytes can result from the transplantation of different types of stem cells. Accordingly, due to its remarkable benefits, stem cell therapy has received attention in recent years as it provides a drug-free and surgical treatment for patients and encourages a more safe and feasible cardiac repair. Although different clinical trials have reported on the promising benefits of stem cell therapy, there is still uncertainty about its mechanism of action. It is important to conduct different preclinical and clinical studies to explore the exact mechanism of action of the cells. After reviewing the pathophysiology of MI, this study addresses the role of tissue regeneration using various materials, including different types of stem cells. It proves some appropriate data about the importance of ethical problems, which leads to future perspectives on this scientific method.